Person-centred care in osteoarthritis and inflammatory arthritis: a scoping review of people’s needs outside of healthcare - Jessica L. Fairley; Maheeka Seneviwickrama; Sabrina Yeh; Shane Anthony; Louisa Chou; Flavia M. Cicuttini; Kaye Sullivan; Andrew M. Briggs; Anita E. Wluka (BMC Musculoskeletal Disorders, 2021)
Abstract Background Arthritis, regardless of cause, has significant physical, social and psychological impacts on patients. We aimed to identify the non-healthcare needs perceived by patients with inflammatory arthritis (IA) and osteoarthritis (OA), and to determine if these differ. Methods We electronically searched MEDLINE, PsycINFO, EMBASE and CINAHL (1990–2020) systematically to identify non-healthcare-related needs of people with IA or OA. All citations were screened and quality appraised by two reviewers. Data was extracted by a single reviewer. Results The search identified 7853 citations, with 31 studies included (12 for OA, 20 for IA). Six areas of need emerged and these were similar in both group These were: 1) Assistance with activities of daily living especially related to a lack of independence; 2) Social connectedness: need for social participation; 3) Financial security: worry about financial security and increased costs of health-seeking behaviours; 4) Occupational needs: desire to continue work for financial and social reasons, facilitated by flexibility of workplace conditions/environment; 5) Exercise and leisure: including limitation due to pain; 6) Transportation: limitations in ability to drive and take public transport due to mobility concerns. Many areas of need were linked; e.g. loss of employment and requiring support from family was associated with a sense of “failure” and loss of identity, as social isolation. Conclusions This review highlights the pervasive impact of arthritis on peoples’ lives, regardless of aetiology, albeit with a limited evidence base. Improved identification and targeting of non-healthcare needs of people with arthritis is likely to improve person-centred care.